Internalization of Sufism Values in the Millennial Generation in Nuralwala - Hamdi, Bil (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
Modern life, with its various materialistic patterns, has caused a spiritual crisis for humanity. As for the millennial generation, it is the generation that lives in this chaotic era, the one most affected by this crisis. This is the condition that drives Nuralwala as an educational institution to move to spread the teachings of tasawuf in this modern era. This research aims to find out three things. First, what is the definition of Sufism Values according to Nuralwala? Second, how Nuralwala's efforts in internalizing the values of taxawuf in the millennial generation. Third, how the outcomes and impact on the millennial generations. This research uses qualitative method with a descriptive-analytic approach. This research has led to the following conclusions: First, understanding the sufism values according to Nuralwala. Second, the effort made by Nuralwala in internalizing the value of tasawuf in the millennial generation is still online education, in which the concrete effort has only touched the cognitive aspect. Third, the outcomes and impacts for the millennial generation are reviewed from three aspects: cognitive, affective and psychomotor. Of these three, the internalization in the cognitive and affective aspects has the outcome and impact for the millennials. In contrast, the results and impact are minimal in the psychomotor aspects.